Organization 2.0: efficiency in tagging - Borovac, Mislav (Array, 2012)
Due to inflation of data and information our idea in this paper is to research the efficiency in tagging and folksonomy. The flexibility of tagging allows users to classify their collections of items in the ways that they find useful, but the personalized variety of terms can present challenges when searching and browsing. The research is going to be conducted by giving fresh-man students, with no prior know ledge of tagging, article of chosen subject in Delicious. Based only on title, subtitle and abstract of the article every student is supposed to assign tags to that article and do the same after reading the whole article. The same procedure is going to be repeat-ed with postgraduate students from the Department of Information Sciences. The aim of our research is to analyze and compare user tags and to point out the connection between tagging by more advanced user and tagging by average user. We believe that the research will surface an enormous difference in the number of tags and in relevance which could be improved by implementing a tag suggestion tool. The most important goals of the pap er are to determine whether tagging can solve the problem of organizing knowledge in contemporary environments and organizations, suggest ways in which this can be achieved and to stress the importance of Organization 2.0 by tagging in Web 2.0 environment.